Resistance to bacterial antibiotics, antiseptics and disinfectants a manifestation of the survival and adaptation mechanisms. (Colombia Medica, 2007)
Resistance to multiple substances is a problem of public health coming to world-wide level observation since the appearance of antibiotics. Indiscriminate use of antibiotics and the environmental selective pressure made by antiseptics and disinfectants have generated a survival answer in the microorganisms, enabling them to efficiently evade the bactericidal action of some agents. Nowadays the time has come to try to explain if mechanisms shared among antibiotics, antiseptics and disinfectants allow bacteria and other germs to activate genes that potentially express the five mechanisms proposed until now as an evolutionary answer to man’s intervention. The present review examines the state-of-the-art of the mentioned mechanisms, with emphasis about the resistance mechanisms performed by nosocomial bacteria in hospitals centers.